(untitled) (Numerus academy review, 2026)
Anthropological research takes its striking vitality from that plurality / diversity that characterizes the human cultural system; renewed diversity according to the coordinates of time and space, where cultural manifestations vary from one group to another, according to an innate system of difference framing human tendencies moral / belief and behavioral, but the anthropological research was not To do so - as a cognitive orientation that seeks to reveal the existential elements of the other / different - otherwise the diversity obtained at the level of social and cultural performances. Thus, research in the system of "difference" and "differentiation / differentiation" is the characteristic by which the understanding of the "other" is established, as it is the diversity that embodies the image of human existence in its religious, linguistic, ethnic and other aspects.